Protective effect of Artemisia absinthium on 6-hydroxydopamine-induced toxicity in SH-SY5Y cell line - Roghayeh Rashidi; Ahmad Ghorbani; Hasan Rakhshandeh; Seyed Hadi Mousavi (Mashhad University of Medical Sciences, 2021)
Objective: Parkinson's disease (PD) is a neurodegenerative disorder characterized by loss of dopaminergic neurons. Several experimental studies have shown neuroprotective and antioxidant effects for Artemisia absinthium. The present study was designed to assess the effect of A. absinthium on 6-hydroxydopamine (6-OHDA)-induced toxicity in SH-SY5Y cells. Materials and Methods: SH-SY5Y cells were treated with ethanolic extract of A. absinthium for 24 hr and then, exposed to 6-OHDA (250 μM) for another 24 hr. MTT (3-(4, 5-dimethylthiazol- 2-yl)-2, 5-diphenyl tetrazolium bromide) assay was used for evaluation of cell viability. Moreover, the rate of apoptosis was measured using propidium iodide (PI) staining. The amount of intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) was also measured using 2', 7'-dichlorofluorescin diacetate (DCFDA) fluorometric method. Determination of glutathione (GSH) and superoxide dismutase (SOD) activity was done by colorimetric assay using DTNB [5, 5'-Dithiobis (2-nitrobenzoic acid)] and pyrogallol respectively. Results: While 6-OHDA significantly increased ROS and apoptosis (p<0.001), the extract of A. absinthium significantly reduced ROS and cell apoptosis at concentrations ranging from 6.25 to 25 μg/mL (p<0.01 and p<0.001 respectively). Also, the extractsignificantly reduced MDA level in comparison with 6-OHDA (p<0.001). The GSH level and SOD activity were increased by the extract. Conclusion: Findings of the current study showed that A. absinthium exerts it effect throughinhibiting oxidative stress parameters and it can be considered a promising candidate to be used in combination with the conventional medications for the treatment of neurodegenerative disorders, such as Parkinson's disease.